DAMPAK PENGELOLAAN BARANG MILIK DAERAH TERHADAP KINERJA DINAS PENDIDIKAN DAN KEBUDAYAAN DI KABUPATEN KEPULAUAN MERANTI TAHUN 2015-2016 - Tengku Kamaruzaman; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the management of fixed assets (Regional Property) should be made a thorough work plan as well as the existence of a working mechanism in order to achieve the objectives of the organization concerned to the fullest. Problems in how the problem of research formulated Regional Property management impacts on the performance of the District Education Office in Kepulauan Meranti Year 2015-2016. The purpose of this study was to determine the effects of management on the performance of Regional Property Office of Education in Kepulauan Meranti Regency Year 2015-2016. This study used a descriptive approach with qualitative methods. This research is located in the Department of Education and Culture Meranti Islands District. The informants are people who provide information and conditions related to the research problem that staff at the Department of Education and Culture Meranti Islands District. Data collection techniques used were observation, interviews and documentation. Data analysis using descriptive methods.The results of this study can be concluded that the Regional Property management on the performance of the District Education Office in Kepulauan Meranti Year 2015-2016 a significant impact on performance, because there are a couple of cycles of Property Management Areas that have not been going well. Efforts Department of Education and Culture Meranti Islands regency to overcome the obstacles of human resources inadequate and poorly maximum auxiliary board items inside the asset management area, is conducting technological guidance regarding the management of local goods. Keywords: Impact Management, Regional Property, PerformanceKeywords: Monitoring, Provider License Early Childhood Education